IMPLEMENTASI PEMBELAJARAN AGAMA ISLAM BERBASIS MULTIMEDIA DI PONDOK PESANTREN - Unang Wahidin; Muhammad Sarbini; Ali Maulida; Miftah Wangsadanureja (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
The objectives of this study were to: (1) obtain data related to multimedia support for Islamic religious learning materials; (2) describe the ease of obtaining multimedia that will be used in the learning process; (3) knowing mudarris skills in using multimedia; (4) knowing the availability of time to use multimedia; and (5) describe multimedia according to the students' level of thinking. The research method used is descriptive qualitative, with data collection techniques of observation, documentation and interviews. The results showed that: (1) multimedia provides convenience in achieving learning objectives; mastery of learning materials; convey the content of religious learning materials as a whole; able to transform abstract religious learning material into concrete; able to combine learning material to be concise; and clarify the information on the content of religious subject matter; (2) multimedia is an inexpensive learning medium; easy to get; easy to manufacture; and easy to use; (3) Islamic boarding school mudarris able to make multimedia for religious learning; able to use multimedia in religious learning; demonstrate the ability to operate multimedia well; and able to explain the advantages and disadvantages of using multimedia; (4) multimedia is able to streamline the delivery time of religious learning materials; able to repeat religious learning material on an ongoing basis; streamline the time of recording religious learning materials; can be used by students to study material outside class hours; presenting complex religious material to be simple; converting religious material that is too broad into the form of films / pictures; the delivery of religious material can be adjusted to the catching power of the students; and religious material that is too large becomes a simpler picture reality; (5) multimedia allows direct interaction between students and the real environment; completeness of learning can be realized; able to equalize the learning experience of students; generate the same perception of religious subject matter; the learning media presented are in accordance with the understanding ability of the students; able to encourage the motivation of students in studying religious material; able to condition the students to concentrate on following religious lessons; and able to bring the boarding school students friendly to technology.